Cambodia trade policy - EUNG, Kimmuyly (KDI School, 2015)
Competition economic power has become the modern-day cold war as indicated by the endless competition in trade and investment. Various theoretical lenses have covered different aspects of how an export-oriented strategy would result in the better development. Yet, there are also beliefs about the fragility of foreign dependency that results from foreign import and investment. The sustainable development can be met only with the complement of import-substitution strategy. This strategy together will promote the domestic private sector which needs strong development for country’s better independence. With the strong foundation of domestic investments, external shocks from imports and foreign investments will no longer be a big obstacle of developments. Moreover, the government’s role as coordinator is a road to success and fast growth of firms both in granting domestic competition and further expanding international markets. Hence, this paper aims to produce a prudent policy recommendation for the Cambodian government with the direction to use import-substitution strategy to promote and sustain the export-led growth. To make an in-depth analysis on the issue, the paper has covered various theories and comparative case studies to find out the best policy outcomes suggested for leapfrog development.
Thesis(Master) --KDI School:Master of Public Policy,2015